Length-weight relationships for 20 species collected in the Jurumirim reservoir (Paranapanema Basin, Brazil) - Oliva-Paterna, F. J.; Torralva, M.; Carvalho, Edmir Daniel [UNESP] (Wiley-Blackwell, 2009)
Length-weight relationships were estimated for 20 species of the Jurumirim reservoir (southern Brazil): one Pimelodidae, one Callichthyidae, six Characidae, one Prochilodontidae, six Anastomidae, one Erythrinidae, two Curimatidae, one Paradontidae and one Cichlidae. The fishes were collected during 2001-2002 using three different types of fishing gear that allowed collection of both adult and juvenile specimens. The first reference of length-weight relationships for 12 species is provided.